The soft drinks companion : a technical handbook for the beverage industry / Maurice Shachman - Shachman, Maurice
Presenting key issues related to the technology of the soft drinks industry, The Soft Drinks Companion: A Technical Handbook for the Beverage Industry discusses both general and advanced technical issues, while allowing for theoretical discussion and academic debate. Drawing on more than thirty-five years of hands-on experience in the technical management of soft drinks facilities, the author deals with subjects in